Tissue damage control confers host tolerance to infection - Soares, Miguel P. (Henry Stewart Talks, 2012)
Host defense strategies against pathogenic microorganisms and parasites, Expression of stress-responsive genes provide tissue damage control, uncoupling different forms of stress associated with inflammation and immunity from tissue damage and disease, Tissue damage control confers host tolerance to infection, Heme oxygenase-1 is a stress-responsive gene that provides tissue damage control, Heme oxygenase-1 confers host tolerance to Plasmodium infection, Preservation of Heme oxygenase-1 system during human evolution